2019
DOI: 10.1111/jfpe.13271
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Brazil nut kernel oil using green solvents: Effects of the process variables in the oil yield and composition

Abstract: The extraction efficiency of isopropyl alcohol and ethyl alcohol was studied, and the effects of the process variables, static time (St), solvent‐to‐feed (S/F) ratio, and temperature (T) in the oil extraction yield (X0), free fatty acids (FFA) content, total phenolic content (TPC), and β‐sitosterol content were statistically investigated. The amount of solvent used (S/F) did not influence the X0, but St and T significantly influenced (p < .05) the X0. The condition that maximized the X0 (60.40%) occurred when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…For oil extraction, there is evidence in the literature that short-chain alcohols such as ethanol and isopropanol could replace hexane in vegetable oils extraction [ 20 , 23 , 25 , 26 , 27 , 51 , 52 ], but the presence of water is detrimental to the oil solubility or recovery [ 30 , 53 , 54 , 55 , 56 ]. Our results are consistent with the trends reported in the literature, since a higher hydration level of the extracting solvent decreased the oil extraction yield.…”
Section: Resultsmentioning
confidence: 99%
“…For oil extraction, there is evidence in the literature that short-chain alcohols such as ethanol and isopropanol could replace hexane in vegetable oils extraction [ 20 , 23 , 25 , 26 , 27 , 51 , 52 ], but the presence of water is detrimental to the oil solubility or recovery [ 30 , 53 , 54 , 55 , 56 ]. Our results are consistent with the trends reported in the literature, since a higher hydration level of the extracting solvent decreased the oil extraction yield.…”
Section: Resultsmentioning
confidence: 99%
“…The total phenolic content was determined according to the method reported by Cornelio-Santiago et al (2019). To obtain the extracts, approximately 2 g of ice cream were weighed, 2 mL of methanol were added in a 10 mL capacity tube, and then they were homogenized in a Vortex mixer at 2,500 rpm for 20 min.…”
Section: Determination Of Total Phenolic Content (Tpc) In Ice Creammentioning
confidence: 99%
“…Cornelio‐Santiago et al (2019) studied the efficiency of oil extraction from the kernels of the Brazil nut by PLE according to the solvents used (isopropyl alcohol and ethyl alcohol) and the process conditions. The main fatty acids identified in the oils, as well as in the method by Soxhlet, were 18:1 and 18:2 acids.…”
Section: Current and New Oilseed Extraction Processesmentioning
confidence: 99%
“…The main fatty acids identified in the oils, as well as in the method by Soxhlet, were 18:1 and 18:2 acids. The authors evaluated the method as a promising technique for obtaining Brazil nut oil, primarily due to its shorter extraction time and the reduced volume of solvent required (Cornélio‐Santiago et al, Cornelio‐Santiago et al, 2019). No studies were found in the literature on the use of PLE for the extraction of oils from seeds of the species of Plukenetia and Caryocar .…”
Section: Current and New Oilseed Extraction Processesmentioning
confidence: 99%